Matching the demographic and work profile of employees to workplace bullying and employee silence - Musa, Norimah; Wok, Saodah (Kolej Universiti Islam Melaka, 2019)
Workplace bullying may lead to employee silence in many organizations. As such, this study attempts to examine the existence of employee silence, which might have a negative effect on organizational productivity and profitability. The objectives of the study are (1) to find out the extent of the existence of workplace bullying and employee silence among employees of a higher learning institution, (2) to analyze the differences among types of demographic characteristics and work-related information in relation to workplace bullying and employee silence, and (3) to determine the relationship between workplace bullying and employee silence. The pilot study was conducted at Open University Malaysia (OUM) among 50 respondents using the survey method with the questionnaire as the research instrument for data collection. Results show that workplace bullying is comparatively less prevalent. However, employee silence does exist. Non-academic staff members are more likely to exhibit silence compared to academic staff members. Also, there is a positive relationship between workplace bullying and employee silence in the higher learning institution. Hence, the spiral of silence theory does apply to the academic sphere.